2020
DOI: 10.21037/atm-20-6873
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of key genes in triple negative breast cancer and validation of oncogene PLK1

Abstract: Background: Breast cancer is the most common malignancy in women. Triple-negative breast cancer (TNBC) refers to a special subtype that is deficient in the expression of estrogen (ER), progesterone (PR), and human epidermal growth factor receptor 2 (HER-2). In this study, a variety of bioinformatics analysis tools were used to screen Hub genes related to the occurrence and development of triple negative breast cancer, and their biological functions were analyzed.Methods: Gene Expression Omnibus (GEO) breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…GEPIA is an internet database that may be utilized to do online research. A substantial amount of sequencing data is available on the GEPIA website, including ndings from 8587 tumors samples and 9736 normal tissues (34).…”
Section: Validation Analysis Of Hub Genesmentioning
confidence: 99%
“…GEPIA is an internet database that may be utilized to do online research. A substantial amount of sequencing data is available on the GEPIA website, including ndings from 8587 tumors samples and 9736 normal tissues (34).…”
Section: Validation Analysis Of Hub Genesmentioning
confidence: 99%
“…Nowadays, use of gene expression profile to define as prognostic biomarkers of TNBC patients have been still under-investigation. Although other studies found the genes related to poor prognosis, those finding have not applied in clinical practice (10)(11)(12)(13). To develop the new prognostic indicators, more detailed research is required owing to the complex tumor heterogeneity and complicated molecular regulatory mechanism of TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics can conduct in-depth analysis of open biological databases such as tissues, cell genes, and proteins, and provide a potential theoretical basis for cancer early diagnosis and treatment ( Wang Y. et al, 2021 ). Many scholars have used the database to analyze differentially expressed genes (DEGs) in the progression of lung cancer, gastric cancer, breast cancer, and other tumors ( Ren et al, 2020 ; Wang H. et al, 2021 ; Shan et al, 2021 ). The proteins encoded by these DEGs could be used as molecular markers for tumor diagnosis and prognosis ( Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%